Religious and Spiritual Dimensions of the Kris: Exploring the Enthusiast’s Perspective - Ismail, Muchammad; Maksum, Ali; Riyanto, Riyanto; Khalifah, Siti (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This article investigates the religious and spiritual dimensions of the kris which is a cherised cultural heirloom. This research aims to portray the deepest meaning of the kris according to the kris enthusiasts in East Java. It is essential to see the kris from local knowledge perspectives. In exploring the meaning of the kris as a sacred object, the article puts forth two main questions: how the kris enthusiasts view the kris as a cultural symbol and how religious and spiritual experiences of the kris influence their views on daily life. This research uses a qualitative method with a combination of phenomenology and ethnography approaches. Data collection was through in-depth interviews, observation, and documentation, with informants selected using purposive sampling. The results of the research show that firstly, the kris enthusiasts view the kris as a religious symbol that helps build their journey of life. The kris is understood as a symbol of noble values and to contain a philosophy of life that is inseparable from other elements, including beliefs, moral values, art, thoughts and practices, thereby being of great importance for the lives of the kris enthusiasts. Secondly, the religious and spiritual experiences of the kris are not limited to external or ritualistic aspects alone, but also encompass the internal dimension that gives birth to spiritual and religious depth, creating a space of meaning for profound human experience.